Evaluation of possible effects of Persea americana seeds on female reproductive hormonal and toxicity profile - Orabueze, Ifeoma C.; Babalola, Rahmotallah; Azuonwu, Obioma (Elsevier, 2021)
Ethnopharmacological relevance: The seed of Avocado (Persea americana, Lauraceae), non-edible part of the fruit is used as health product. It has been reported as traditional female contraceptive and sterilizer in Peru and some Asian countries and in Nigeria as cardio-protective agent. The present study focused on the effect of hydro-methanolic seed extract of Persea americana on female hormones and toxicity profile using animal models. Materials and methods: The serum follicle stimulating hormone (FSH) and progesterone (PROG) concentrations in mature non-pregnant female rats were assayed using hormonal kits. The toxicity profile was assessed using Lorke's acute toxicity model, haemato-biochemical evaluation and histopathological studies of reproductive related organs. Parameters were measured on day-30, 60 and 90. Presence of biomarker flavonoid compounds were confirmed using High Performance Liquid Chromatography. Results: The extract at 20, 100 and 500 mg kg -1 altered FSH and PROG hormone profile of the treated groups. The extract initially, dose-dependently decreased FSH level in day-30 (6.95, 3.97, 2.08 IU/L respectively) compared to untreated group before a significant increase was observed for day 60 and 90. Progesterone increased dose-dependently in the treated groups throughout the 90-day treatment duration. This may be Indicating cumulative effect on the hormone. No deleterious or toxicity effect was noticed. Conclusions: The extract of Persea americana seed affects female hormone activity. This may find application in various hormonal management procedures, maternal and reproductive health and fertility control/help health facilities. However, it should be used with caution in women intending to conceive.
Keywords: Female hormone; Follicle stimulating hormone (FSH) and progesterone; Toxicity; University of Lagos; ACEDHARS; ACE: Drug Research, Herbal Medicine Development and Regulatory Science; Ini-Ibehe Okoko; George Asare